Changes in colloid solution sales in Nordic countries. Issue 4 (7th January 2018) - Kongsgaard, U. E.; Holtan, A.; Perner, A.
Abstract : Background: Administration of resuscitation fluid is a common intervention in the treatment of critically ill patients, but the right choice of fluid is still a matter of debate. Changes in medical practice are based on new evidence and guidelines as well as traditions and personal preferences. Official warnings against the use of hydroxyl‐ethyl‐starch (HES) solutions have been issued. Nordic guidelines have issued several strong recommendations favouring crystalloids over colloids in all patient groups. Our objective was to describe the patterns of colloid use in Nordic countries from 2012 to 2016. Methods: The data were obtained from companies that provide pharmaceutical statistics in different countries. The data are sales figures from pharmaceutical companies to pharmacies and health institutions. Results: We found a 56% reduction in the total sales of all colloids in Nordic countries over a 5‐year period. These findings were mainly related to a 92% reduction in the sales of HES solutions. A reduction in sales of other synthetic colloids has also occurred. During the same period, we found a 46% increase in albumin sales, but these numbers varied between Nordic countries. Conclusion: The general reduction in colloid sales likely reflects the recommendation that colloids should be used only in special circumstances. The dramatic reduction in the sales of HES solutions was expected given evidence of harm and the official warnings. The steady increase in albumin sales and the notable differences between the five Nordic countries cannot be explained.